Phytomitogen responses of peripheral blood lymphocytes in young and older subjects - Foad, B. S. I. (1974)
Quantitation of the response of peripheral blood lymphocytes to the phytomitogens phytohaemagglutinin-M, concanavalin A, and pokeweed mitogen was compared in thirteen young subjects and thirteen older subjects. Both dose of phytomitogen and duration of lymphocyte culture were evaluated. Younger individuals had higher responses to all three phytomitogens after 3 days of culture, whereas older individuals had higher responses after 5 days of culture. The concentration of phytomitogens required to produce maximal stimulation in both groups varied with culture duration.